Determinación del contenido de fibra, grasa y proteína de un alimento nutricional con semillas (lupinus mutabilis, y chenopodium quinoa), en mezcla de (beta vulgaris y cucurbita máxima) y edulcorantes - Carbajal Parrales, Cindy Katherine (2016)
This research was aimed at determining the content of fiber, fat and protein of a nutritional food with seed in mixture of vegetables and sweeteners. The elaboration of the yogurt and the analyzes were carried out in the laboratories of the Faculty of Engineering in Agricultural Sciences in the State Technical University of Quevedo. Three factors were applied with two levels seeds; chocho and quinoa, vegetables; beets and squash, and sweeteners; stevia and panela. In the experimental phase it was used for data processing a factorial arrangement A x B x C. The characteristics of the experiment were 3 repetitions, 8 treatments which gives a total of 24 experimental units made up of 100 g of sample for each of the analysis. The physicochemical indicators, rheological, proximal, sensory and microbiological certain guarantee a good quality product and safe. Is evaluated the results for the identification of the treatment with best features the same that turned out the treatment a1b0c0 (Quinua x Beet x Stevia), with an acidity titrable in base acid lactic in 1.11%; pH (4.32); ° Brix (15.50%); Viscosity (Cp 400,77); Fiber (8.43%); Fat (0.53%); Protein (17.83%); Calcium (23.79%); Energy (5,51 Kcal); Ash (0.47%); Humidity (78,65%); Total solids (19.53%) microbiological analysis of E.coli, total coliforms, molds and yeasts showed that there was no pollution in the final product. Sensory analysis was conducted of texture, color, taste, aroma and overall acceptability